SOME ISSUES OF THE DEVELOPMENT OF THE SOCIAL STATE IN THE CIS COUNTRIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to the examination of the approaches to the content of the concept of social state and its significance for the CIS countries. In addition, the article investigates some aspects of the formation and development of the social state in the CIS. Furthermore, the article studies the impact of the demographic factor, which is considered one of the social problems observed in the countries of the world, the characteristics of the demographic situation in these countries, as well as provides analisys performed in reliance upon the criteria of standard indicators.